2008
DOI: 10.1007/s10661-008-0676-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical contamination assessment of Gulf of Mexico oysters in response to hurricanes Katrina and Rita

Abstract: Hurricane Katrina made landfall on August 29, 2005 and caused widespread devastation along the central Gulf Coast states. Less than a month later Hurricane Rita followed a similar track slightly west of Katrina's. A coordinated multi-agency response followed to collect water, sediment and tissue samples for a variety of chemical, biological and toxicological indicators. The National Oceanic and Atmospheric Administration's National Status and Trends Program (NS&T) participated in this effort by measuring chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…Among the seven contaminants that were found to have increased in oyster tissues, five were heavy metals. This reaffirms the observation that metal body burdens are most likely to increase in oysters after a severe storm (Johnson et al 2009).…”
Section: Impacted Year 1989-hurricane Florence and Tropical Storm Keithsupporting
confidence: 86%
See 1 more Smart Citation
“…Among the seven contaminants that were found to have increased in oyster tissues, five were heavy metals. This reaffirms the observation that metal body burdens are most likely to increase in oysters after a severe storm (Johnson et al 2009).…”
Section: Impacted Year 1989-hurricane Florence and Tropical Storm Keithsupporting
confidence: 86%
“…For example, after Hurricane Katrina, chemical analysis of floodwaters revealed that several metals and organic contaminants were in excess of the US Environmental protection Agency (EPA) threshold for human health exposure (Presley et al 2005). Similarly, in tissues of oysters exposed to subsiding storm surge and floodwater after Katrina, significant increases of trace metal concentrations were observed (Johnson et al 2009). These efforts, though localized, resulted in some significant findings that are relevant for an integrated ecosystem impact assessment after severe storms.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in detection methods, increased epidemiological surveillance, and efforts by authorities to improve the quality of products put on the market have contributed to better recognition of viral contamination. These improvements have assisted in identifying that increases in human populations in coastal areas, as well as climate change, inducing heavy rainfall and associated sewage overflows, constitute risk factors for shellfish contamination (3,4).…”
mentioning
confidence: 99%
“…In that context, sedimentary resuspension may have resulted in periodic exposure of the trace organic contaminants in this study. Sediment resuspension events have been demonstrated to result in greater bioaccumulation of metals by oysters in the Gulf of Mexico (JOHNSON et al, 2009). Given that all the sampling collection areas are interidal and shallow-subtidal, oysters from these areas are exposed to sediment re-suspension through wind-and tidal-driven forces as well as boat wakes.…”
Section: Trace Organic Contaminant Concentrations In Oyster Tissue -Cmentioning
confidence: 99%